Environmentally sensitive fluorescence of the topical retinoid adapalene - Soler-Orenes, Juan A.; Monari, Antonio; Miranda, Miguel A.; Hernández-Gil, Javier; Lhiaubet-Vallet, Virginie (Frontiers in Chemistry, 2024)
Intrinsic fluorescence of drugs brings valuable information on their localization in the organism and their interaction with key biomolecules. In this work, we investigate the absorption and emission properties of the topical retinoid adapalene in different solvents and biological media. While the UVA/UVB absorption band does not exhibit any significant solvent-dependent behavior, a strong positive solvatochromism is observed for the emission. These results are in line with molecular modeling and simulations that show the presence of two quasi-degenerate states, i.e a local π-π* and an intermolecular charge-transfer (ICT) state. However, molecular modeling also revealed that, whatever the solvent, at the corresponding equilibrium geometry the lowest and emissive excited state is the local π-π *. Finally, the potential of adapalene to act as a biological probe is demonstrated using albumin, DNA and micelles.